Family Support and Challenges in Caring for Disabled Children in Malaysia: A Review of Literature - Jamir Singha, Paramjit Singh; Azmana, Azlinda; Drania, Syazwani; Ahmadb, Aznan Che; Mohd Nora , Mohd Iqbal Haqim (International Journal of Psychosocial Rehabilitation, 2020)
Purpose - This paper aims to review the literature related to family support and challenges in caring for disabled children in Malaysia.Design/methodology/approach - A systematic search of studies published between 1994 to 2019 in American Academy of Pediatrics, Oxford University Press, Cambridge University Press, Routledge, SAGE Online, Springer Link, Taylor & Francis Online, Humanities and Social Sciences Collections, Wiley Online Library and Health Collections was undertaken to examine the support and challenges faced by families in caring for children with disabilities.Findings - Studies have proven that family members faced a lack of psychological and structural support in caring for children with disabilities. This has led to an increase of challenges including social exclusion, stigma and discrimination, lack of academic structure and unmet healthcare needs for children with disabilities. Addressing shortcomings is vital to allow these children to prosper as an important member of society and fulfil their potential as human beings.Originality/value - This paper is not currently under consideration, in press or published elsewhere. Effective collaboration between various agencies by providing more psychological and structural support for families and children with disabilities could enhance their social function and wellbeing. This can reduce negative implications on families and children with disabilities as well.